Gross morphometry of young Geochelone sulcata (Testudines: Testudinidae) in Costa Rica - Merchán, Manuel (2005)
The African Spur tortoise, Geochelone sulcata, has been introduced to Costa Rica. A total of 31 tortoises were measured for 26 gross morphometry parameters. All individuals measured were inmature, aged from 5 to 34 months, and were born in captivity in La Garita de Alajuela, Costa Rica. Mean straight carapace length was 83.1 mm, mean straight plastron length was 68.3 mm and mean maximum height was 46.2 mm. All the measurements were correlated, except tail length and cloacal distance. Weight had the highest positive allometry coefficient. All the variables were joined in two Principal Components; tail length and cloacal distance in Factor 2 and the rest of them in Factor 1. Lack of correlation among tail measures and the other variables as well as their inclusion in a different Factor could be related with an incipient development of sexual dimorphism characters